2017
DOI: 10.1186/s12913-017-2176-5
|View full text |Cite
|
Sign up to set email alerts
|

Transitions from biomedical to recovery-oriented practices in mental health: a scoping review to explore the role of Internet-based interventions

Abstract: BackgroundThe Internet is transforming mental health care services by increasing access to, and potentially improving the quality of, care. Internet-based interventions in mental health can potentially play a role in transitions from biomedical to recovery-oriented research and practices, but an overview of what this may entail, current work, and issues that need addressing, is lacking. The objective of this study is to describe Internet-based recovery-oriented interventions (referred to as e-recovery) and cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 90 publications
(121 reference statements)
0
29
0
Order By: Relevance
“…Our own scoping review of e-recovery found 20 studies of six recovery-oriented portals in five countries [47]. These studies have promising, but as yet no definitive findings related to enhanced shared decision making [48], strengths and resilient self-care strategies [49], social connectedness and empowerment [7,50], and patient-centered care [51,52], to mention a few.…”
Section: Discussionmentioning
confidence: 99%
“…Our own scoping review of e-recovery found 20 studies of six recovery-oriented portals in five countries [47]. These studies have promising, but as yet no definitive findings related to enhanced shared decision making [48], strengths and resilient self-care strategies [49], social connectedness and empowerment [7,50], and patient-centered care [51,52], to mention a few.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation of recovery-oriented practices in mental health is demonstrated to be challenging [47][48][49][50]. While offline peer support is established as integral to recovery-oriented practice, research into the role that online peer support might play in shaping recovery processes in mental health care is still in its formative stages [51,52]. Online and offline formats for peer support groups have qualities that are potentially complementary and research into the possible outcomes of interactions between the two formats has been called for [23].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating digital health interventions and peer support into existing mental health services presents a way forward. Strand et al’s [ 24 ] recent scoping review asserted that “e-recovery” can “potentially facilitate recovery-oriented care” (p. 11) in mental health services. Peer support was central to five of six interventions included in their review, of which two involved experience-sharing with peers through forums, stories, or videos [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%